Persistence of Women in Online Degree-Completion Programs - Müller, Terry (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2008)
Although online courses at postsecondary institutions promise adults access, flexibility, and convenience, many barriers to online learning remain. This article presents findings from a qualitative case study, which explored the phenomenon of undergraduate and graduate women learners’ persistence in online degree-completion programs at a college in the Northeast of the United States. Research questions asked why women learners persisted or failed to persist, and how factors supporting or hindering persistence influenced learners. Interviews with a purposeful sample of 20 participants revealed the complexity of variables affecting learners’ persistence to graduation. Findings suggested that multiple responsibilities, insufficient interaction with faculty, technology, and coursework ranked highest as barriers to women’s persistence. Strong motivation to complete degrees, engagement in the learning community, and appreciation for the convenience of an online degree-completion option facilitated persistence.